Mosaic loss of the Y chromosome in human neurodegenerative and oncological diseases - I. L. Kuznetsova; L. I. Uralsky; T. V. Tyazhelova; T. V. Andreeva; E. I. Rogaev (Вавиловский журнал генетики и селекции, 2023)
The development of new biomarkers for prediction and early detection of human diseases, as well as for monitoring the response to therapy is one of the most relevant areas of modern human genetics and genomics. Until recently, it was believed that the function of human Y chromosome genes was limited to determining sex and controlling spermatogenesis. Thanks to occurance of large databases of the genome-wide association study (GWAS), there has been a transition to the use of large samples for analyzing genetic changes in both normal and pathological conditions. This has made it possible to assess the association of mosaic aneuploidy of the Y chromosome in somatic cells with a shorter lifespan in men compared to women. Based on data from the UK Biobank, an association was found between mosaic loss of the Y chromosome (mLOY) in peripheral blood leukocytes and the age of men over 70, as well as a number of oncological, cardiac, metabolic, neurodegenerative, and psychiatric diseases. As a result, mLOY in peripheral blood cells has been considered a potential marker of biological age in men and as a marker of certain age-related diseases. Currently, numerous associations have been identified between mLOY and genes based on GWAS and transcriptomes in affected tissues. However, the exact cause of mLOY and the impact and consequences of this phenomenon at the whole organism level have not been established. In particular, it is unclear whether aneuploidy of the Y chromosome in blood cells may affect the development of pathologies that manifest in other organs, such as the brain in Alzheimer’s disease, or whether it is a neutral biomarker of general genomic instability. This review examines the main pathologies and genetic factors associated with mLOY, as well as the hypotheses regarding their interplay. Special attention is given to recent studies on mLOY in brain cells in Alzheimer’s disease.